Crossover Food Businesses in Louisiana, United States: A Descriptive Study of Their Characteristics and Food Safety Training Needs From Public Health Inspectors' Perspective - Wenqing Xu; Evelyn Watts; Carolyn Bombet; Melissa Cater (Korean Society for Preventive Medicine, 2022)
Objectives Integrating retail and manufacturing enables limitless potential for food businesses, but also creates challenges for navigating within complex food safety regulations. From public health inspectors' (PHIs) perspective, this study aimed (1) to describe the characteristics of crossover businesses in Louisiana, and (2) to evaluate regulation awareness and food safety education needs for business owners and PHIs who inspect crossover businesses. Methods A self-administered questionnaire was administered to Louisiana Department of Health PHIs using Qualtrics®. A descriptive analysis was performed, focusing on the frequency of each item. Results In total, 1774 retailers were conducting or planned to conduct specialized processes, while 552 food manufacturers were performing or planned to perform retail functions. Reduced oxygen packaging, the use of additives such as vinegar as a method of preservation, and smoking food as a method of preservation were observed by 62%, 36%, and 35% of the PHIs, respectively. The PHIs perceived crossover businesses as "not aware" or "somewhat aware" of the food safety regulations. The current food safety training level for these businesses was reported to range from "no training" to "some training but not sufficient." When asked for a self-assessment, the majority of PHIs reported themselves as being "familiar" with the variance requirement for specialized processing. Their confidence in inspecting crossover businesses, however, leaned towards "not confident" or "somewhat confident." Conclusions To better guard public health, food safety training is needed for crossover food business owners, as well as PHIs, on regulations and conducting or inspecting specialized processes.